Study the Effect of Peganum Harmala Seeds Extracts to Protect Iron Alloy from Corrosion in Salt Media - Abdulameer Abbas, Hayfaa (Iraqi Journal of Science, 2023)
This work describes the inhibition effect of different concentration of an aqueous extract of Peganum harmala seed on the corrosion of carbon steel in 3.5 % sodium chloride solution using potentiostatic polarization techniques at the temperature range of 25°C to 55°C. The result show that inhibition efficiency increased with increasing concentration of the inhibitor extracts and temperature. The adsorption of inhibitor on carbon steel surface was fit into Langmuir adsorption isotherm. Kinetic and thermodynamic parameters governing the corrosion and adsorption process were calculated and discussed.